An International Year to Celebrate Nursing (2020)
ABSTRACT: On 16 May 2019, the 72nd World Health Assembly designated 2020 as the International Year of Nursing. The decision was made by bearing in mind the substantial contribution made by this profession to the population’s health, and that this year marks the bicentennial of the birth of Florence Nightingale, one of the founders of modern nursing.